Antigenic Analysis of Bordetella pertussis Filamentous Hemagglutinin with Phage Display Libraries and Rabbit Anti-Filamentous Hemagglutinin Polyclonal Antibodies - Wilson, Dan R. (American Society for Microbiology, 1998)
Although substantial advancements have been made in the development of efficacious acellular vaccines against Bordetella pertussis, continued progress requires better understanding of the antigenic makeup of B. pertussis virulence factors, including filamentous hemagglutinin (FHA). To identify antigenic regions of FHA, phage display libraries constructed by using random fragments of the 10-kbp EcoRI fragment of B. pertussis fhaB were affinity selected with rabbit anti-FHA polyclonal antibodies. Characterization of antibody-reactive clones displaying FHA-derived peptides identified 14 antigenic regions, each containing one or more epitopes. A number of clones mapped within regions containing known or putative FHA adhesin domains and may be relevant for the generation of protective antibodies. The immunogenic potential of the phage-displayed peptides was assessed indirectly by comparing their recognition by antibodies elicited by sodium dodecyl sulfate (SDS)-denatured and native FHA and by measuring the inhibition of this recognition by purified FHA. FHA residues 1929 to 2019 may contain the most dominant linear epitope of FHA. Clones mapping to this region accounted for ca. 20% of clones recovered from the initial library selection and screening procedures. They are strongly recognized by sera against both SDS-denatured and native FHA, and this recognition is readily inhibited by purified FHA. Given also that this region includes a factor X homolog (J. Sandros and E. Tuomanen, Trends Microbiol. 1:192–196, 1993) and that the single FHA epitope (residues 2001 to 2015) was unequivocally defined in a comparable study by E. Leininger et al. (J. Infect. Dis. 175:1423–1431, 1997), peptides derived from residues of 1929 to 2019 of FHA are strong candidates for future protection studies.